A study on the rate of gastric digestion in Tilapia nilotica fingerling fed with mixed chlorella vilgaris beyerinck and tetraselmis chuii chu. - Tingson, Pedro Fanega Jr. (1980.)
Twenty four Tilapia nilotica fingerlings were obtained and fed with mixed Chlorella vulgaris Beyerinck and Tetraselmis chuii Chu for the determination of the rate of gastric digestion. The rate of gastric digestion was measured by the percentage decrease in dry weight of the stomach contents taken every hour for three hours. Eight fingerlings were placed in three 14 liters capacity plastic pails and starved for two days. Then, they were fed with mixed Chlorella and Tetraselmis at 2 of their body weight for one hour. After the feeding time, two fishes were taken from each container and their stomach contents examined for the initial amount of food ingested (0 hr). Three periods at one hour interval each ( 1hr,2hr,3hr) were set for the examination of stomach contents. Two fishes were picked up at random from each container every hour and their stomach dissected. The percentage decrease in dry weight of stomach contents were 15.06 (1st hr), 22.87 (2nd hr) and 54.47 (3rd hr).
Research Paper (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Tilapia